ANTIMICROBIAL STEWARDSHIP IN VETERINARY MEDICINE: PREVALENCE OF STEWARDSHIP PROGRAMS AND PRELIMINARY ANTIMICROBIAL USE DATA - Ramjisingh, Jovita (My University, 2019)
This applied practice experience was undertaken for 242 hours at the Dispensary at the Veterinary Health Center at Kansas State University from September 2018 to March 2019. The Veterinary Health Center at Kansas State University (VHC) is a full-service veterinary hospital that provides routine, specialty, and emergency care. The Dispensary at the VHC plays a crucial role in providing unparalleled services filling prescriptions for their patients. Antimicrobial resistance is defined by the Centers for Disease Control and Prevention as microorganisms that mutate to evade the antimicrobials used to treat them. Antimicrobial resistance is an international public health crisis because antimicrobial resistant infections may spread to others and increase mortality rates. As antimicrobial resistance becomes a growing public health concern in human health, the prevalence of antimicrobial stewardship programs in human hospitals has increased exponentially. Similar to human health, antimicrobial stewardship programs for veterinary use should integrate infection prevention and control, whilst implementing judicious antimicrobial prescribing. Although veterinary medicine would benefit from antimicrobial stewardship programs, lack of person power and time are major barriers hindering the implementation of these programs. The Veterinary Health Center at Kansas State University prescribes a broad range of antimicrobials for therapeutic use as do most veterinary hospitals. The purpose of this applied practical experience was to analyze the frequency, dose, duration, indication and overall prescribing patterns of one of those antimicrobials, amoxicillin-clavulanate, in canine and feline patients at the VHC. The main objective was to help determine prescribing patterns of this medication, as baseline data to be used in the implementation of an antimicrobial stewardship program at the VHC. In addition to analyzing these data, a survey was sent to veterinary teaching hospitals across the United States and Canada to develop a deeper understanding of veterinary antimicrobial stewardship programs in these settings. Applying the knowledge gained from this applied practical experience has provided me with a deeper One Health understanding of antimicrobial resistance.
Keywords: antimicrobial resistance; stewardship; amoxicillin-clavulanate; one health; veterinary hospital